The determining cross-section width of discrete restraining structures - Shapoval, Volodymyr; Ponomarenko, Ivan; Shashenko, Dmytro; Grigoryev, Alexey (Academic journal Industrial Machine Building Civil Engineering, 2021)
Currently, there is no single method for determining the width of the cross-section for the elements of anti-landslide retaining structures with a rectangular cross-section (or the diameter of the elements with a round cross-section) at a known distance between them. An algorithm for determining the diameter (in the case of a transitional view of a round shape) or the smaller side (in the case of a transverse transition of a rectangular shape) of anti-vessels supporting structures at a known distance between them is presented. In the course of the above work, obtained analytical dependencies that allow us to determine: the width of the cross-section for the elements of anti-slip retaining structures with a rectangular cross-section (or the diameter of the elements with a round cross-section) at a known distance between them, the step of arranging the elements of anticonvulsant supporting structures with a rectangular cross-sectional shape (or the diameter of the elements of a circular cross-sectional shape) at a known distance between them.
Keywords: landslide; retaining structure; diameter element; width element; step elements